2019
DOI: 10.1111/1467-8500.12389
|View full text |Cite
|
Sign up to set email alerts
|

Linking transformational leadership and value congruence among Chinese police force: The mediating role of goal clarity and the moderating role of public service motivation

Abstract: Although claimed as an important value assimilating factor within public administration, transformational leadership's effect over value congruence receives limited empirical investigation. Furthermore, the underlying mechanism and boundary condition of this effect are underspecified. Drawing from an interactionist perspective whereby value congruence is the joint product of situational influence and individual characteristic, this study investigates the relationship between transformational leadership and val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 126 publications
(209 reference statements)
0
5
0
Order By: Relevance
“…Research on public sector conducted by Bao & Ge, (2019) found a moderating effect of work motivation on transformational leadership and police performance in China. Research performed by Adriansyah et al, (2020) examined the mediating effect of motivation between transactional leadership style and organizational culture on organizational performance at Police Office in Malang, Indonesia.…”
Section: Mediation Relationship: Motivation Mediates the National Pol...mentioning
confidence: 98%
“…Research on public sector conducted by Bao & Ge, (2019) found a moderating effect of work motivation on transformational leadership and police performance in China. Research performed by Adriansyah et al, (2020) examined the mediating effect of motivation between transactional leadership style and organizational culture on organizational performance at Police Office in Malang, Indonesia.…”
Section: Mediation Relationship: Motivation Mediates the National Pol...mentioning
confidence: 98%
“…Inter alia, PSM indicates the officials' personal goals are less important than the community aspirations and goals and public service is important for their overall satisfaction with their professional occupation (Bao & Zhong, 2023; O'Leary, 2019; Perry & Wise, 1990). For instance, it was shown how the Chinese public officials upheld their professional values to evince transformational leadership for bringing about the desired administrative churn affecting society (Bao & Ge, 2019). That said, PSM is associated with the extent to which an employee is engaged in her work and the same is reflected in her work commitment (Mussagulova, 2021) but non‐congruent results were attested in another research wherein PSM was not found to have any bearing on job satisfaction (Rayner et al, 2018).…”
Section: Related Researchmentioning
confidence: 99%
“…Research on public sector conducted by Bao & Ge, found a moderating effect of work motivation on transformational leadership and police performance in China [28]. Research performed by Adriansyah et al, examined the mediating effect of motivation between transactional leadership style and organizational culture on organizational performance at Police Office in Malang, Indonesia [29].…”
Section: Mediation Relationship: Motivation Mediates the National Pol...mentioning
confidence: 99%